Influence of testing environment on static fatigue behavior of a glass and a polycrystalline ceramic - Fraga,Sara (2021)
Abstract It aims on evaluate the effect of the test environment on static fatigue behavior of lithium disilicate-based (LD), and yttrium oxide-stabilized zirconia (YSZ) ceramics. Specimens of LD (IPS e.max CAD, Ivoclar Vivadent) and YSZ (IPS e.max ZirCAD MO, 3 mol% Y2O3, Ivoclar Vivadent) were randomly allocated into three groups: tested in air, inert (paraffin oil, Sigma Aldrich) or distilled water. The static fatigue test (n=15) was performed using a piston-on-three ball assembly, adapted from ISO 6872, as follows: starting load 100 N for LD and 300 N for YSZ; loading application time set to 1 hour for each loading step; step size of 50 N for LD and 100 N for YSZ, applied successively until fracture. Data from static fatigue strength (MPa) and time to fracture (hours) were recorded. Fractographic analysis was executed. Survival analysis corroborates absence of influence of environment on static fatigue outcomes (fatigue strength, time to fracture and survival rates) for YSZ. For LD, specimens tested in air presented statistically superior survival rate and static fatigue strength (p= 0.025). In regards of time to fracture, LD tested in air were superior than when tested in distilled water (p=0.019) or inert (p=0.017) environments. No statistical differences for Weibull modulus were observed. Failures started on the tensile stress surface. Thus, the test environment did not affect slow crack growth (SCG) mechanisms during static fatigue test of YSZ ceramics, but it plays a significant role for the static fatigue behavior of lithium disilicate-based glass ceramics, indicating a high susceptibility to SCG.